ANALYSIS OF STUDENT LEARNING ACTIVITY IN THE FIRST MIDDLE SCHOOL OF JAMBI CITY - Nur Ika Sandi Pratiwi; Astalini Astalini; Dwi Agus Kurniawan (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2021)
The purpose of this study was to determine the activeness of student learning in science subjects at Junior high school 18 Jambi City, Junior high school 21 Jambi City, and Junior high school 24 Jambi City. The research method used is a mixed research method with an explanatory design. The research subjects were students of Junior high school 18 Jambi City, students of Junior high school 21 Jambi City, and students of Junior high school 24 Jambi City, totaling 567 students. The data analysis technique used descriptive statistics for quantitative data and Miles Huberman's analysis for qualitative data. The results of the study on the three indicators show that students are categorized as having good learning activeness on the indicator